Impact of weight loss and disease progression on survival in ALS: insights from a multidisciplinary care center - Dourado Junior, Mário Emílio Teixeira; Dourado, Laura Carvalheira; Santana, Glauciane Costa; Vale, Sancha Helena de Lima; Leite-Lais, Lucia (Arquivos de Neuro-Psiquiatria, 2025)
Amyotrophic lateral sclerosis (ALS) is a multifaceted neurodegenerative disorder with a poor prognosis. Weight loss and malnutrition emerge as significant clinical features during disease progression.To explore how demographic and clinical characteristics relate to survival in ALS patients, emphasizing the role of weight loss percentage at the time of diagnosis.We conducted a retrospective study that used the database of a multidisciplinary ALS care center in the city of Natal, Brazil.A total of 132 patients were included in the study. The mean age of the participants at symptom onset was of 56.9 years, and most of them were male (59.8%). Older age, bulbar onset, and faster disease progression were associated with weight loss ≥ 10% at diagnosis. Among 132 patients, 72% experienced death or tracheostomy, with a median survival of 34 months. Survival was notably reduced in patients aged ≥ 60 years, those with significant weight loss, rapid disease progression, or those submitted to gastrostomy. Weight loss and the rate of disease progression were the strongest predictors of reduced survival. Potential factors relating gastrostomy with reduced survival are discussed.The present study highlights the critical impact of weight loss and disease progression on survival in ALS patients, emphasizing the importance of early nutritional and clinical interventions. These findings underscore the need for comprehensive, multidisciplinary care strategies to address key prognostic factors and improve outcomes in ALS patients.
Keywords: Amyotrophic Lateral Sclerosis; Weight Loss; Disease Progression; Nutritional Status; Survival Analysis